Validity of mock-witness measures for assessing lineup fairness - Lee, Jungwon (Psychology, crime & law, 2022)
Although eyewitness researchers have used mock-witness measures to assess aspects of lineup fairness, they have paid little attention to their validity. The current study tested predictive validity, convergent validity, and discriminant validity of mock-witness measures from a meta-analytic perspective. Overall, mock-witness measures had predictive validity, particularly in target-absent (TA) lineups – the lineup fairness estimated by the measures reliably predicted eyewitnesses’ choosing behaviors and discriminability of a suspect from fillers in TA lineups. However, correlations between lineup fairness estimated by mock-witnesses and eyewitness performance were significant in target-present (TP) lineups only when eyewitnesses had a moderate memory for the perpetrator. Multitrait-multimethod correlations demonstrated significant intradomain correlations between mock-witness measures and other lineup fairness indices and nonsignificant interdomain correlations between the mock-witness measures and indices reflecting memory strength for the perpetrator, which supported convergent validity and discriminant validity, respectively. The implications for research and practice are discussed.